Hybrid subcarrier multiplexing SAC-OCDMA deploying MS-code over free space optical link for Malaysia weather condition - Al-Nassar, Ghusoon Abdulameer Erhayem (2018)
In recent years, free space optics (FSO) transmission systems are gradually being explored as alternatives to replace or to complement the available optical fibre and wired communication due to its low cost, ease of installation, higher data rate, larger bandwidth and licence-free installation. As the aforementioned benefits come into the lime light, the large available bandwidth can essentially be benefited from, for multiple-user systems. Records have shown the effectiveness of a hybrid SCM-SAC-OCDMA in achieving greater capacity and enhanced security in FSO. Nevertheless, the available codes used suffered from many limitations such as dependency solely on prime numbers (as in the MQC code), code weight being limited to even numbers (as in the KS code) and rigid code construction as the number of users increases (as in the MD code). The Multi-Service (MS) code has the advantage of flexibility and being dynamic as any number of code weights can be constructed without altering the wavelength of the existing light source. The code equally benefits from short length and sparsely located chips which could prevent cross-talk and hence could improve the performance of the system. Therefore, this research aims at investigating and improving multi-user FSO systems by proposing a hybrid subcarrier multiplexing SAC-OCDMA technique using the MS code with direct decoding technique. The performance are observed under different weather conditions which include clear, rain, and haze with Malaysia as a case study. The investigation began by analysing the proposed system in mathematical modelling (using MATLAB) and simulation software (using OptiSystem) employing the Light Emitting Diode (LED) source. The subsequent works were then carried out using laser source as a result of the limitations in LED. The effects of increasing the number of code words as well as subcarriers at different distances and data rates were observed. The performance of the MS code based system was subsequently compared with KS, MD and MQC codes under clear, rainy and hazy weather conditions. Finally, the performances of the MS code under different angles of beam divergence and types of noise were evaluated based on bit error rate (BER), received power, eye diagram, and transmission distance. At the bit rate of 1 Gb/s and BER threshold of 10−9 , heavy rain in the proposed system indicated the worse performance compared to clear weather and heavy haze as it reduced the transmission distance from 6.3 km (in clear weather) to 0.9 km. Nevertheless, under clear weather conditions with attenuation coefficient of 0.233 dB/km, the system designed using the MS code out-performed the KS, MD and MQC systems as it is capable of supporting up to 6.3 km, which is 0.8 km, 0.9 km and 1.5 km farther than KS, MD and MQC codes respectively in six-user channels. In conclusion, this study has provided a means of improving FSO communication which suits the weather conditions in Malaysia and other tropical zones.